LITERATUR REVIEW: APLIKASI EKSTRAK TANAMAN DALAM MENGENDALIKAN PENYAKIT BUSUK PANGKAL BATANG YANG DISEBABKAN JAMUR PATOGEN GANODERMA BONINENSE - Muthia Ridala; Dezi Handayani (Jurnal Biogenerasi, 2026)
Stem base rot in oil palm caused by Ganoderma boninense is one of the main factors contributing to reduced productivity. Currently, control still relies on synthetic fungicides. However, their continuous use has the potential to cause negative environmental impacts. Therefore, more environmentally friendly control alternatives are needed, one of which is through the use of plant extracts. This study aims to assess the potential of plant extracts as antifungal agents in controlling basal stem rot base on a systematic literature review. The method used is a Systematic Literature Review (SLR) following the PRISMA guidelines through the steps of identification, screening, eligibility, and included. Data sources were obtained from various platforms such as Google Scholar, SpringerLink, and ScienceDirect, with article inclusion criteria ranging from 2016 2026. The results of the review indicate that various plant extracts, such as Asystasia gangetica, Curcuma longa, Cerbera manghas, Senna multijuga, and Elettaria cardamomum, exhibit antifungal activity against G. boninense. Their effectiveness is influenced by the plant species, the part used, the extraction method, the solvent, and the concetration. The mechanisms of action include cell membrane damage, disruption of permeability, and inhibition of pathogenic enzymes. Thus, plant extracs have the potential to be developed as an effective, environmentally friendly and sustainable botanical fungicide alternative for controlling basal stem rot in oil palm.